2013
DOI: 10.1371/journal.pone.0075532
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Cells Are Involved in the Susceptibility of NADPH Oxidase Knockout Mice to 6-Hydroxy-Dopamine-Induced Neurodegeneration

Abstract: We explored the impact of Nox-2 in modulating inflammatory-mediated microglial responses in the 6-hydroxydopamine (6-OHDA)-induced Parkinson’s disease (PD) model. Nox1 and Nox2 gene expression were found to increase in striatum, whereas a marked increase of Nox2 expression was observed in substantia nigra (SN) of wild-type (wt) mice after PD induction. Gp91phox-/- 6-OHDA-lesioned mice exhibited a significant reduction in the apomorphine-induced rotational behavior, when compared to wt mice. Immunolabeling assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…Recently, several studies have implicated Nox1-derived ROS in dopaminergic cell death induced by paraquat and 6-OHDA, and both of these toxins upregulated Nox1 (Choi et al, 2012; Cristovao et al, 2012; Hernandes et al, 2013). NADPH oxidase- and mitochondria-derived ROS both play equally important key roles in proinflammatory microglial activation (Dikalov, 2011; Mead et al, 2012; Bordt and Polster, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have implicated Nox1-derived ROS in dopaminergic cell death induced by paraquat and 6-OHDA, and both of these toxins upregulated Nox1 (Choi et al, 2012; Cristovao et al, 2012; Hernandes et al, 2013). NADPH oxidase- and mitochondria-derived ROS both play equally important key roles in proinflammatory microglial activation (Dikalov, 2011; Mead et al, 2012; Bordt and Polster, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxin-induced dopaminergic degeneration in the substantia nigra depends on expression of NOX2 (Gao et al, 2003;Wu et al, 2003;Hernandes et al, 2013). However, curiously, treatment of gp91phox(À/À) mice with minocycline results in enhanced microglia activation and neuronal loss relative to wild-type mice also treated with minocycline (Hernandes et al, 2013). Disregarding non-cell-autonomous effects, these data, together with the observations of Block et al (Taetzsch et al, 2015), suggest that NOX2 activity can be required for anti-inflammatory effects in M2-activated microglia.…”
Section: Nrf2mentioning
confidence: 99%
“…The antibiotic minocycline selectively inhibits development of the M1, but not the M2, activation response (Kobayashi et al, 2013). Neurotoxin-induced dopaminergic degeneration in the substantia nigra depends on expression of NOX2 (Gao et al, 2003;Wu et al, 2003;Hernandes et al, 2013). However, curiously, treatment of gp91phox(À/À) mice with minocycline results in enhanced microglia activation and neuronal loss relative to wild-type mice also treated with minocycline (Hernandes et al, 2013).…”
mentioning
confidence: 99%
“…In support of this contention, NOX1 expression has been reported to increase after striatal injection of 6-OHDA and is associated with a simultaneous increase in DNA oxidative stress [216]. Additionally, following 6-OHDA induction, there is an increase in NOX1 and NOX2 gene expression in the mouse striatum, and NOX2 expression in the substantia nigra [217]. In vivo and in vitro studies of PD induced by paraquat have shown increased expression of NOX1 and synucleins [217].…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, following 6-OHDA induction, there is an increase in NOX1 and NOX2 gene expression in the mouse striatum, and NOX2 expression in the substantia nigra [217]. In vivo and in vitro studies of PD induced by paraquat have shown increased expression of NOX1 and synucleins [217]. NOX2 expression has also been shown to increase in mouse brains after administration of MPTP [218] and to be elevated in PD human brains [218].…”
Section: Introductionmentioning
confidence: 99%